Molecularly Imprinted Electrochemical Sensor-Based Fe2O3@MWCNTs for Ivabradine Drug Determination in Pharmaceutical Formulation, Serum, and Urine Samples - Abdel-Haleem, Fatehy M.; Gamal, Eman; Rizk, Mahmoud S.; Madbouly, Adel; El Nashar, Rasha M.; Anis, Badawi; Elnabawy, Hussam M.; Khalil, Ahmed S. G.; Barhoum, Ahmed (Frontiers in Bioengineering and Biotechnology, 2021)
Ivabradine hydrochloride (IVR) is a medically important drug because of its ability to lower the heart rate. Techniques reported for IVR determination were expensive, laborious, besides being of poor selectivity. In this study, iron oxide @ carbon nanotube (Fe2O3@CNTs) nanocomposite and molecularly imprinted polymer (MIP) were synthesized and used in the fabrication of carbon paste electrodes (CPEs) for the potentiometric detection of IVR in biological and pharmaceutical samples. CPEs of the best sensor were formulated from graphite (41 wt%) as a carbon source, MIP (3 wt.%) as an ionophore, Fe2O3@CNTs (5 wt%) as a modifier, and nitrophenyl octyl ether (NPOE, 51 wt.%) as a conductive oil so-called plasticizer. The best sensor exhibits a Nernstian slope (response) of 56 mV decade-1 within the IVR concentration range from 1.0x10-3 M to 9.8x10-8 M with high selectivity against interfering species (ascorbic, maltose, glucose, lactose, dopamine, glycine) over those reported earlier. The use of Fe2O3@CNTs together with MIP in the electrode formulation was found to improve the limit of detection (LOD) from 630 nM to 98 nM along with high reversibility, a short response time of 30 sec, and a good lifetime of more than two weeks. The sandwich membrane (SMM) method was used to quantify the H-bonding complexing strength of the MIP binding sites for IVR with Log βILn=11.33. The constructed sensors were successfully applied for the IVR determination in blood serum, urine, and commercial formulations (Savapran®) with high sensitivity.